2003
DOI: 10.1128/jb.185.18.5491-5499.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dominantly Negative Mutant ClyA Cytotoxin Proteins in Escherichia coli

Abstract: We report studies of the subcellular localization of the ClyA cytotoxic protein and of mutations causing defective translocation to the periplasm in Escherichia coli. The ability of ClyA to translocate to the periplasm was abolished in deletion mutants lacking the last 23 or 11 amino acid residues of the C-terminal region. A naturally occurring ClyA variant lacking four residues (183 to 186) in a hydrophobic subdomain was retained mainly in the cytosolic fraction. These mutant proteins displayed an inhibiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 33 publications
5
63
0
Order By: Relevance
“…Furthermore, ClyA is not subject to any signal sequence cleavage and there is no evidence of any other posttranslational modification (3,8,23,30,45). The finding that ClyA accumulates in the periplasmic space when overproduced in E. coli has indicated that the ClyA secretion pathway includes toxin translocation to the periplasm (3,23,42,43,47). It has also been demonstrated that ClyA can subsequently be released from E. coli cells by blebbing of outer-membrane vesicles (42).…”
mentioning
confidence: 76%
“…Furthermore, ClyA is not subject to any signal sequence cleavage and there is no evidence of any other posttranslational modification (3,8,23,30,45). The finding that ClyA accumulates in the periplasmic space when overproduced in E. coli has indicated that the ClyA secretion pathway includes toxin translocation to the periplasm (3,23,42,43,47). It has also been demonstrated that ClyA can subsequently be released from E. coli cells by blebbing of outer-membrane vesicles (42).…”
mentioning
confidence: 76%
“…Cytoplasmic, periplasmic, and membrane fractions were obtained following procedures described previously (38).…”
Section: Methodsmentioning
confidence: 99%
“…Other groups report MV production to be an alternate secretion pathway capable of directing bacterial products, including cytotoxins (10,11), enzymes (5), and DNA (10,12), to prokaryotic and eukaryotic cells. For example, Helicobacter pylori produce vacuolating cytotoxin A-containing MVs (13,14), and E. coli and Salmonella typhi produce cytolysin A-containing MVs (15,16), which are cytotoxic to mammalian cells. P. aeruginosa MVs are found in biofilm matrices (17), contain the quorum-sensing molecule 2-heptyl-3-hydroxy-4-quinolone (18), and fuse with unrelated Gram-negative and Gram-positive bacteria (19,20), suggesting MVs function as signals in biofilm formation and interspecies intraspecies bacterial population biology.…”
Section: Embrane Vesicles (Mvs)mentioning
confidence: 99%